2022
DOI: 10.3390/genes13061098
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Rare Genetic Variants of Immune Mediators as Risk Factors for Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) affects more than 1% of children, and there is no viable pharmacotherapeutic agent to treat the core symptoms of ASD. Studies have shown that children with ASD show changes in their levels of immune response molecules. Our previous studies have shown that ASD is more common in children with folate receptor autoantibodies. We also found that children with ASD have abnormal gut immune function, which was characterized by a significant increase in the content of immunoglobulin A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The effect of FRAAs on ASD severity has been investigated [29][30][31][32]. One study found that those with blocking FRAAs had more favorable development and metabolic profiles than those with binding FRAAs, and those with binding FRAAs had higher B12 concentrations in the blood than those with blocking FRAAs [33].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of FRAAs on ASD severity has been investigated [29][30][31][32]. One study found that those with blocking FRAAs had more favorable development and metabolic profiles than those with binding FRAAs, and those with binding FRAAs had higher B12 concentrations in the blood than those with blocking FRAAs [33].…”
Section: Discussionmentioning
confidence: 99%
“…Given the small sample size of our study, failing to pass the Bonferroni correction threshold could be expected, thus all genes with a p < 0.005 in the SKAT-O analysis were moved forward to functional follow-up. Setting the threshold at p < 0.005 for SKAT-O analysis could provide signi cant ndings of rare variants, and many studies have already identi ed interesting signals using a higher p-value threshold in SKAT-O analysis [29][30][31]. Further, there was a lack of functional studies and modi er gene validations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the small sample-size of our study, failing to pass the Bonferroni correction threshold could be expected, thus all genes with a p < 0.005 in the SKAT-O analysis were moved forward to functional follow-up. Setting the threshold at p < 0.005 for SKAT-O analysis could provide significant findings of rare variants, and many studies have already identified interesting signals using a higher p -value threshold in SKAT-O analysis [ 36 , 37 , 38 ]. Further, there was a lack of functional studies and modifier gene validations.…”
Section: Discussionmentioning
confidence: 99%